Aryeh Neier Public Lecture - The Global Movement for Human Rights: Successes and Failures
Recording of the fourth public lecture given by Aryeh Neier, President of the Open Society Institute and Founder of Human Rights Watch. The lecture entitled "The Global Movement for Human Rights: Successes and Failures" was held at the CEU Auditorium on October 16, 2001 and was part of a week of special events planned to celebrate CEU’s Tenth Anniversary. The lecturer was introduced by President and Rector of the CEU, Yehuda Elkana. Contains the Q&A session as well.